Effect of supplementation and withdrawal of selenium-enriched kale sprouts on productivity and egg selenium concentration of laying hens - Anut Chantiratikul; Pinyada Thongpitak; Orawan Arunsangseesod; Eakapol Wangkahart; Kwanyuen Leamsamrong; Worapol Aengwanich; Juan Boo Liang; Wu Xin; Piyanete Chantiratikul (Animal Bioscience, 2023)
Objective The aim of this trial was to investigate the effect of supplementation and withdrawal of selenium-enriched kale sprouts (SeKS) on productivity and egg Se concentration of laying hens. Selenium from commercial Se-enriched yeast (SeY) was used as a comparative Se source. Methods One-hundred and eighty 61-week-old laying hens were randomly divided into 5 treatment groups with 4 replicates (9 hens each) in a 2×2+1 Augmented Factorial Experiment in a completely randomized design. The experimental diets were basal diet, basal diet supplemented with 0.2 and 0.4 mg Se/kg from SeKS and SeY, respectively. The 8-week feeding trial was divided into 2 periods, namely the Se supplemental period (week 1 to 4) and the Se withdrawal period (week 5 to 8). Results Productive performance, egg quality and egg Se concentration of laying hens were not affected by sources of Se (SeKS and SeY) during both, the Se supplemental and withdrawal periods. Egg production and egg Se concentration increased (p<0.05) with increasing levels of Se supplementation. The egg Se concentration increased and reached a peak 1 week after Se supplementation. However, concentration of Se in eggs of hens fed Se from both sources decreased rapidly from the second week of the Se withdrawal period to reach the same egg Se concentration of hens fed the basal diet by the fourth week of the Se withdrawal period. Conclusion The efficacy of Se from SeKS on productivity and egg Se concentration in laying hens was comparable to commercial SeY. Thus, SeKS can provide an alternate organic Se source for production of Se-enriched eggs.